2021
DOI: 10.1021/acs.jmedchem.1c00862
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Phosphodiesterase-9 Inhibitors for the Treatment of Hepatic Fibrosis

Abstract: Hepatic fibrosis commonly exists in chronic liver disease and would eventually develop to cirrhosis and liver cancer with high fatality. Phosphodiesterase-9 (PDE9) has attracted profound attention as a drug target because of its highest binding affinity among phosphodiesterases (PDEs) with cyclic guanosine monophosphate. However, no published study has reported PDE9 inhibitors as potential agents against hepatic fibrosis yet. Herein, structural modification from a starting hit LL01 led to lead 4a, which exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…A more recent study showed that overexpression of PDE4D in the liver led to the development of NAFLD and hypertension in mice, which was attenuated by PDE4 inhibitor treatment [60]. Beyond PDE4, recent papers have shown a role of PDE9 and 10 in liver and lung fibrosis as well as diet-induced obesity [61][62][63][64]. Our data show a significant upregulation of PDE9A and 10A in the livers of AH patients (Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…A more recent study showed that overexpression of PDE4D in the liver led to the development of NAFLD and hypertension in mice, which was attenuated by PDE4 inhibitor treatment [60]. Beyond PDE4, recent papers have shown a role of PDE9 and 10 in liver and lung fibrosis as well as diet-induced obesity [61][62][63][64]. Our data show a significant upregulation of PDE9A and 10A in the livers of AH patients (Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…AutoMD, a MD-based virtual screening approach 26 , was applied in the present study. AutoMD includes the establishment of pharmacophore model, molecular docking and dynamics simulations, and free energy prediction.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated levels of cAMP and/or cGMP have been found to have antifibrotic effects by inhibiting the myofibroblast-driven ECM production. Thus, several PDE inhibitors have been used to investigate the antifibrotic effects in different liver fibrosis animal models. For example, the PDE5 inhibitor tadalafil could improve portal hypertension and reduce liver fibrosis induced by bile duct ligation (BDL) in rats. , The PDE3 inhibitor cilostazol could protect rats from alcohol-induced liver fibrosis by suppressing the TGF-β/CTGF activation and the cAMP/EPAC1 signal. , Our group developed a PDE9 inhibitor 4a , which showed significant antifibrotic effects in a BDL-induced rat model …”
Section: Introductionmentioning
confidence: 99%